Pemberdayaan dan Partisipasi Perempuan Pengusaha Kecil Industri Kreatif Berorientasi Peningkatan Kinerja Pemasaran Berbasis Orientasi Pasar - Santoso, Aprih; Kurniawati, Emaya (Jurnal Riptek, 2023)
The aim of this study is to empirically analyze the effect of market orientation on marketing performance with product innovation as a mediating variable for women small entrepreneurs in creative industries in Pedurungan District, Semarang City. The research sample used was 117 people obtained by the census method. The relationship model between variables will be analyzed using path analysis (SPSS'26). Based on the test results, it was found that market orientation and product innovation had a significant and positive effect on marketing performance for women small entrepreneurs in creative industries in Pedurungan District, Semarang City. and Product innovation as a mediating variable was able to mediate the effect of market orientation on marketing performance for women entrepreneurs in small creative industries in Pedurungan District, Semarang City.